PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN BAGIAN PRODUKSI KELAPA SAWIT PADA PT. PERKEBUNAN NUSANTARA V KEBUN SEI GALUH - Riyanto, Agung; Hendriani, Susi; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2018)
This research aims to determine the influence of leadership andorganizational culture on job satisfaction and employee performance of palm oilproduction at PT. Perkebunan Nusantara V Kebun Sei Galuh. This research usedprimary data which obtained from interviews and questionnaires to all employeesat PT. Perkebunan Nusantara V Kebun Sei Galuh. Secondary data obtainedrelated to the object and organizational structure. The sample of the research wasall employees who numbered 150 people. The analytical method used in thisresearch was using path analysis (path analysis) with the help of SPSS program.From result of the test which have been done, there was direct influencebetween leadership to performance equal to 0,689, indirect influence betweenleadership to performance through job satisfaction equal to 0,1867, directinfluence between organizational culture to performance equal to 0,784, indirectinfluence between organizational culture to performance through job satisfactionequal to 0.760, and the effect of job satisfaction on the performance equal to0.271, so the total effect was 1.181. Result of calculation of coefficient ofdetermination (R2) was equal to 0.954 which mean, leadership variable andorganizational culture through job satisfaction influence to employeeperformance equal to 95,4%, while the rest 4,6% influenced by other variablesnot examined in this research.